LANGUAGE ASSESSMENT AND TESTING IN A DIGITAL AGE - Mamadiyorova Sevara Olimjon qizi (Western European Studies, 2024)
The digital age, that is, the rapid development of information and communication technologies, creates new opportunities and challenges for the processes of education and language learning. Today, language assessment and testing methods are also changing and integrating with digital technologies. In this article, we discuss the importance, methods and possibilities of language assessment and testing in the digital age
Keywords: digital technologies; language; traditional methods